Functional and radiological outcomes of impaction grafts and cemented cup for the treatment of acetabular bone deficiency in total hip arthroplasty - Maysara A Bayoumy; Mohamed M Mohamed (Wolters Kluwer Medknow Publications, 2021)
Background and Aim Acetabular bone defects are one of the most difficult problems in both primary and revision total hip replacements. Many techniques have been described to deal with acetabular bone defects in total hip replacement, including the use of cement with or without cages and rings, structural bone grafting, and impaction bone grafts with cementless or cemented cups. The aim of this study was to asses short-term to midterm clinical and radiological outcomes of acetabular reconstruction by impaction bone grafts and cemented cups in both primary and revision cases indicated for total hip arthroplasty (THA) with acetabular bone deficiency. Patients and methods This is a retrospective study that included 26 patients with total hip arthroplasty (THA) who underwent acetabular bone defect reconstructions with grafting and cemented cups between December 2014 and January 2019. The mean age at operation was 45.3 years. Among the procedures, 12 were primary THAs, whereas 14 procedures were revision THAs. The morselized grafts were used in eight cases only, along with combined strut graft and morselized grafts in five cases, acetabular rim mesh and morselized grafts in 12 cases, and Kerboul cross-ring with morselized grafts in one case. All cases were clinically evaluated by Harris hip score in addition to radiological evaluation. Results All the patients except one showed clinical improvement, where the mean postoperative Harris hip score became 84. Radiograph follow-up for all the cases showed graft incorporation without loosening or any significant cup migration, except one case, which was revised owing to loosening around the cup. Conclusion The use of impaction graft and cemented cups is safe and reproductive even in young patients. Moreover, this technique reconstitutes bone and gives a stable platform of bone stock for further revision, especially in young population.